Taxonomía de las paremias en lengua española (PHRASIS | Rivista di studi fraseologici e paremiologici, 2017)
Despite the great development of both paremiology and paremiography, especially in Spanish, there is not a unanimous use of some theoretical concepts, such as in the use of terminology. The proposal to classify the short and sententious statements from the superordinate ”paremia” dates back from a few decades. Said proposal has been and still is well accepted, and also has evolved over time. However, the definition and classification of proverbs remains difficult because of their complex nature, the often misused term ”paremia”, and because there is not an established terminology unanimously accepted by the linguistic community. In this paper we make a review of the main works published up to the present paper in order to provide some terminological and conceptual reflections on proverbs. This way, we try to avoid overlapping and also to establish precise definitions of the different categories of paremiai, mainly the most problematic types: the proverb and the proverbial phrase.
Keywords: Paremiology, paremia, proverb, aphorism